If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -2) = 10 + x Reorder the terms: 3(-2 + 2x) = 10 + x (-2 * 3 + 2x * 3) = 10 + x (-6 + 6x) = 10 + x Solving -6 + 6x = 10 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -6 + 6x + -1x = 10 + x + -1x Combine like terms: 6x + -1x = 5x -6 + 5x = 10 + x + -1x Combine like terms: x + -1x = 0 -6 + 5x = 10 + 0 -6 + 5x = 10 Add '6' to each side of the equation. -6 + 6 + 5x = 10 + 6 Combine like terms: -6 + 6 = 0 0 + 5x = 10 + 6 5x = 10 + 6 Combine like terms: 10 + 6 = 16 5x = 16 Divide each side by '5'. x = 3.2 Simplifying x = 3.2
| (4x-12)+52=90 | | -6(0)+2= | | 3(4x+5)-5(7x-7)=2(6x+1) | | 0=x^2-9x-8 | | -(x+11)=2(2x-6) | | 5*(1/3)-(-2/3)X | | 2(6x-1)=120 | | -30=-14+v | | 4x=4(0+2x) | | 6x+68=9x-7 | | 2x+20+3x+8=180 | | -3=x-15 | | 9sin^2x+2=3 | | 2=2n | | 1x-20=10 | | b-5=-24 | | 5x+85=53 | | (36x)/(-8x) | | 2x+1=6x+(-23) | | 3k=-51 | | 3n+4=7n+4 | | 2+25x=20x+15 | | 3.4x=2.7 | | 5t+6=-24-t | | 36x/-8x | | b/3--17=20 | | y=-0.02x^2+1.6x | | 9x+9=8x+5 | | -2x-8x= | | 3(x-5)=2x+30 | | 2.7x-0.05x+0.75x=3.4x | | v/3-3=1 |